Comparative analysis of the functional outcome of absorbable and non-absorbable suture material used in management of acute Achilles tendon rupture - Kumar, Manoj; Malik, Anzar T.; Rafiq, Shiran; Muzzafar, Khalid; Bijyal, Arpan (International Journal of Research in Orthopaedics, 2025)
Background: Achilles tendon rupture is one of the most common tendon injuries in the adult population. The injury commonly occurs in middle-aged adults. Patients with acute rupture often present with sudden onset of pain at the site of injury and experience difficulty with ankle plantar flexion compared to the normal side. In most cases, patients report a sensation similar to being kicked in the lower leg. Achilles tendon rupture causes significant pain and disability. This study assessed the comparative analysis and functional outcomes of acute Achilles tendon rupture managed by polydioxanone (PDS) (absorbable) suture and polyester (non-absorbable) suture. We prospectively studied acute Achilles tendon rupture in patients over a 1 and ½ year period and reviewed functional outcomes and complications. Methods: Forty-nine patients with acute Achilles tendon rupture were included, with a minimum follow-up period of six months. We used the Boyden score to assess outcomes and complications between the two groups repaired by and polyester (Ethibond), respectively. Results: In our study, all 26 patients (100%) in the PDS (absorbable) group had good or excellent results based on the Boyden clinical assessment, whereas only 13 patients in the polyester repair group had good or excellent results. Conclusions: Patients treated with the non-absorbable polyester (Ethibond) suture material for repair had a higher incidence of infection and foreign body granulomas. Surgical repair with the absorbable suture PDS is superior to polyester, as it results in significantly lower postoperative wound complications and higher patient Boyden scores. However, studies with larger sample sizes are recommended.